Indoor performance of wireless sensor network - Hamdan, Hasri (2012)
Wireless sensor networks have the potential to become significant subsystems of engineering applications where every each node functions as transmitter, receiver, router and data sink. It is necessary to understand the dynamic behaviour of these systems in simulation environments. It is critical to develop simulation platforms that are useful which can be used to explore both networking and wireless sensor networks issues. A discrete-event simulation is a trusted platform for modeling and simulating a variety of systems. This project emphasize on using new simulator for wireless sensor networks that is based on the discrete event simulation framework called Objective Modular Network Test bed in C++ version 4.1 (OMNeT++4.1) Simulator. This simulator is used to test the performance of sensor nodes within the networking in wireless communication networks based on indoor scenario. The test performances are focussed on aspects such as the time delay and packet utilization of the particular approach. The analysis approach is done through simulation software by the following metrics: packet frames delivery, packet loss and time delay experience within the system.